Seed production and its components in Sardinian germplasm of Hedysarum coronarium L. and H. spinosissimum L. - Bullitta S.; Saba P.; Bullita P. (Legumes for Mediterranean forage crops, pastures and alternative uses, 2000)
Local populations of the two species Hedysarum coronarium L. and H. spinosissimum L. from the Sardinian region of Trexenta-Marmilla were examined for the seed yield components and seed production in the frame of a project for the biodiversity conservation and the valorization of local populations of neglected species. Seed losses occurred at harvest for H. coronarium accessions because of the gradual seed maturity reached within each plant, this is a problem for seed production, but considering the utilization of Sardinian prostrate growing sulla as pasture species, such feature could be turned into an useful factor for increasing the soil seed bank and allowing the subsequent plant regeneration from seeds. Preliminary results are encouraging the efforts spent in the valorization of Sardinian germplasm of Hedysarum species in view of its diffusion in dry areas of the Mediterranean basin.
10. Meeting of the Mediterranean Sub-Network of the FAO-CIHEAM Inter-Regional Cooperative Research and Development Network on Pastures and Fodder Crops, 2000/04/04-09, Sassari (Italy)